PRAKTIK EARNINGS MANAGEMENT PERUSAHAAN PUBLIK INDONESIA - ISHAR BAHARUDDIN (Jurnal Bisnis dan Akuntansi, 2008)
The study investigates the practice of earnings management in Indonesian non-financial public companies and the different degree of each industry. It also investigates the impact of earnings management on value relevance of accounting information. Earnings management measures developed in the literatures were adopted to measure the practice in each industries and to examine the relationship between these measures and their impact on the value relevance of accounting information. Descriptive analysis, correlation and regression were applied to data collected from twelve non-financial industries listed in Bursa Efek Indonesia, from year 1999 to 2004. Results show that in general Indonesian non-financial public companies practiced earnings management, of which the real estate and property, agriculture and mining industries are practicing in the highest degree. It was also found that there is no relationship between the earnings management practice and value relevance of accounting information.